Mathematical Model for Population Growth of Lao PDR - BOUALAKHAM, Sengdala; SOUKSOMVANG , Phouvanh; SOUKSOMVANG, Phoui (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this paper is to use mathematical models to predict the population growth of Lao PDR. The Lao PDR is one of the ASEAN countries that the growth rate of population is quite low over the 21 period of years. The Least Square Method, Malthus’s and the logistic growth models are applied to the model to estimate the population growth of Lao PDR using data from 2000 to 2020. The data used was collected from the web of the (World Bank Data). We also use the least square method to compute the best population growth rate of Malthus’s model. All of three models give the Mean Absolute Percentage Error (MAPE) of 0.1216%. The logistic population growth model predicted a growth rate of 2.09% per year and the predicted population in 2025 is 7,826,386 people with the Mean Absolute Percentage Error of 0.1319% while the Malthus’s population growth model predicted a growth rate of 1.157% per year and the estimate population in 2025 is 7,882.684 people with the Mean Absolute Percentage Error of 0.1167%. However, the least square method gives the same growth rate as the Malthus one as 1.57% per year and the predicted population in 2025 is 7,885,942 people with the Mean Absolute Percentage Error is computed as 0.1162%.